For the Salvation of the Cosmos The Church's Mission of Ecojustice - Nothwehr, Dawn M. 1951- (2019)
The Christian ecojustice mission is grounded in the intimate relationship between creation, redemption, and incarnation. Failure to adequately integrate this truth in its mission praxis has obscured Christian proclamation. Mission clarification requires knowing the God of all creation. Mission motivation originates in humans knowing their true identity as ones loved by God within and through creation. Mission correction consists in heeding revelation from the "Book of Creation" (St. Augustine), learning wisdom from "asking of the beasts" (Job 12:7). Not to love, defend, and protect creation is to fail ourselves and God, since we are God's creation.
Keywords: Laudato Si'; Noachian covenant; Deep Incarnation; ecojustice; Interdependence